Allocentric Spatial Performance Higher in Early-Blind and Sighted Adults Than in Retinopathy-of-Prematurity Adults. (March 2016) - Eardley, Alison F.; Edwards, Geoffrey; Malouin, Francine; Kennedy, John M.
The question as to whether people totally blind since infancy process allocentric or external spatial information like the sighted has caused considerable debate within the literature. Due to the extreme rarity of the population, researchers have often included individuals with retinopathy of prematurity (RoP—over oxygenation at birth) within the sample. However, RoP is inextricably confounded with prematurity per se. Prematurity, without visual disability, has been associated with spatial processing difficulties. In this experiment, blindfolded sighted participants and two groups of functionally totally blind participants heard text descriptions from a survey (allocentric) or route (egocentric) perspective. One blind group lost their sight due to RoP and a second group before 24 months of age. The accuracy of participants' mental representations derived from the text descriptions was assessed via questions and maps. The RoP participants had lower scores than the sighted and early blind, who performed similarly. In other words, it was not visual impairment alone that resulted in impaired allocentric spatial performance in this task but visual impairment together with RoP. This finding may help explain the contradictions within the existing literature on the role of vision in allocentric spatial processing.